Applying Knowledge Management in the Empowerment of Volunteers at Perpustakaan Limbah Pustaka Purbalingga: A SECI Model Approach - Winastwan, Rheza Ega; Zidna, Lisda Safarina; Fatwa, Annisa Nur; Kiasati, Almas Inti (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background: Community-based libraries rely heavily on volunteers to sustain their programs and services. However, volunteer empowerment and organizational sustainability can be limited without structured knowledge sharing and management. Limbah Pustaka Library, a community library in Indonesia, has implemented various initiatives to optimize the contribution of its volunteers. Objective. This study explored the importance of knowledge management in empowering volunteers at Limbah Pustaka Library, Purbalingga. The research is motivated by the limited human resources in village libraries and the need for knowledge management strategies to enable volunteers to contribute sustainably to library services and community development.Research Methods. A qualitative descriptive approach was employed. Data were collected through interviews with volunteers and library staff, participant observation of library activities, and review of relevant documents. The data analysis followed a sequential data condensation, presentation, and concluding process.Data Analysis. In addition to descriptive analysis, data were analyzed thematically to identify evidence of each SECI stage and assess its impact on volunteer empowerment. The analysis focused on knowledge sharing and creation patterns corresponding to the SECI processes.Result. The results indicate that all four SECI stages manifested in the volunteer program. Socialization occurred through group discussions and collaborative activities among volunteers; externalization was achieved by documenting volunteers' tacit knowledge into guides and procedures; combination involved integrating various explicit information into shared resources; and Internalization took place through training and hands-on practice. Implementing the SECI model enhanced knowledge sharing and volunteer collaboration, improving service innovation and community engagement.Conclusion. In conclusion, SECI-based knowledge management effectively empowered the Library Wastevolunteers, as evidenced by increased collaboration and innovative service delivery. These findings support using structured knowledge management strategies in community library programs.